The Impact of Numbered Heads Together Model on the Learning Outcomes of Science Viewed from Students’ Self Regulated Learning - Nia Wahyu Wijayanti; Roemintoyo Roemintoyo; Tri Murwaningsih (Journal of Education and Learning (EduLearn), 2017)
This research aims to explain 1) the different impact among Numbered Heads Together (NHT) model and direct instruction on the science learning outcomes. 2) the different effect among the high, medium and low self regulated learning on the students’ learning outcomes of science. 3) the interaction among the learning models and self regulated learning towards the students’ learning outcomes of science. The type of research was quasi-experimental research with factorial design 2×3. Population of this research was all students of fifth grade elementary school. The hypothesis test used two-way analysis variant with unbalanced cells. Based on data analysis, Numbered Heads Together model with high self regulated learning was the most effective.